STUDI ANALISIS FAKTOR FAKTOR YANG MENJADIKAN GURU YANG BAIK - Mahatma, Mahatma (PROGRAM STUDI PENELITIAN DAN EVALUASI PENDIDIKAN, 2021)
Sociologists have long recognized the important role of teachers in education. Teachers have a great influence on shaping a student's personality, knowledge, values, and attitudes towards school. The teacher as a central figure, which in addition to the school climate, academic environment and discipline, is an important element of the school context. Good teachers contribute to the realization of good education. Assessment implies the basic question